2021
DOI: 10.1177/2515690x211064585
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Anti-Inflammatory, Acute Oral Toxicity, and Qualitative Phytochemistry of The Aqueous Root Extract of Launaea cornuta (Hochst. Ex Oliv. & Hiern.)

Abstract: The root and leaf extracts of Launaea cornuta have been locally used in traditional medicine for decades to manage inflammatory conditions and other oxidative-stress-related syndromes; however, their pharmacologic efficacy has not been scientifically investigated and validated. Accordingly, we investigated the in vitro antioxidant activity, anti-inflammatory ( in vitro, ex vivo, and in vivo) efficacy, acute oral toxicity, and qualitative phytochemical composition of the aqueous root extract of L. cornuta. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 62 publications
(141 reference statements)
3
4
0
Order By: Relevance
“…In addition, no pathologic changes were observed in the experimental rats' liver, kidney, and spleen sections. These findings depict the safety of the studied plant extract, at least in Sprague Dawley rats, in line with previous studies [ 24 , 26 , 33 , 38 ] and are further supported by the biochemical, haematological, and physical examination evidence obtained in our study. Moreover, the safety of the studied plant extract may be attributable to the low concentration or absence of some amalgams, which have been demonstrated previously to cause toxicity [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, no pathologic changes were observed in the experimental rats' liver, kidney, and spleen sections. These findings depict the safety of the studied plant extract, at least in Sprague Dawley rats, in line with previous studies [ 24 , 26 , 33 , 38 ] and are further supported by the biochemical, haematological, and physical examination evidence obtained in our study. Moreover, the safety of the studied plant extract may be attributable to the low concentration or absence of some amalgams, which have been demonstrated previously to cause toxicity [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…There are no specific, conventionally harmonised guidelines for the preparation, packaging, storage, distribution, and dosage in traditional medicine, which raises public health and safety concerns [ 22 ]. In addition, there is insufficient pharmacologic data, including herb-herb and herb-synthetic drug interactions, specific indications and contraindications, and associated side effects on various ethnomedicinally important plants like Y. alpina , which hamper their appraisal and potential for integration into the conventional healthcare system [ 9 , 23 , 24 ]. Accordingly, we investigated the subacute toxicity effects of the aqueous shoot extract of Y. alpina to appraise its safety, owing to its extensive ethnomedicinal applications.…”
Section: Discussionmentioning
confidence: 99%
“…These results support those reported by Akimat et al [ 29 ] indicating the non-toxicity of the aqueous root extract of L. cornuta in mice. Given the widespread use of L. cornuta as vegetables, and a medicine for numerous ailments in traditional medicine [ 26 , 28 , 47 ], it was imperative to appraise its safety.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to other uses, it is used to treat gonorrhoea, typhoid, inflammatory diseases including enlarged testicles, earaches, stomach-aches, chronic joint problems, diabetes, hypertension, and memory loss [ 27 , 28 ]. Past studies have shown that this plant is highly effective in reducing inflammation and free radicals, and it also contains antioxidant phytocompounds [ 29 ] that may improve cognitive function [ 30 ]. Even though L. cornuta has been used extensively to treat dementia and associated complications, among other ailments in traditional medicine, there is a paucity of empirical information to appraise its efficacy and medicinal value.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the availability, affordability, and lability of synthetic antioxidants limit their use (Akimat et al, 2021). Dietary supplements have attracted a lot of attention as potential replacements for synthetic antioxidants.…”
Section: Introductionmentioning
confidence: 99%